The Human Resource Function: The Dynamics of Change and Development - Derek Torrington; Laura Hall (Great Britain Financial Times/Pitman Publishing, 1998)
The issue of the changing role of the personnel/HR function is a highly topical one and many of the issues that this raises are of key concern to students and managers alike. This text is unique in spelling out the implications of these changes to human resource management and in encompassing decentralisation and outsourcing.
Keywords: Human Resource Management; Textbooks; The International Market Environment (ECO1021-N); HRM: Contemporary Issues (HRM2074-N)